2020
DOI: 10.1186/s13071-020-04207-x
|View full text |Cite
|
Sign up to set email alerts
|

Biovar-related differences apparent in the flea foregut colonization phenotype of distinct Yersinia pestis strains do not impact transmission efficiency

Abstract: Background: Yersinia pestis is the flea-transmitted etiological agent of bubonic plague. Sylvatic plague consists of complex tripartite interactions between diverse flea and wild rodent species, and pathogen strains. Transmission by flea bite occurs primarily by the Y. pestis biofilm-mediated foregut blockage and regurgitation mechanism, which has been largely detailed by studies in the model interaction between Y. pestis KIM6+ and Xenopsylla cheopis. Here, we test if pathogen-specific traits influence this in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…Thus, an ∼50% reduction in blockage rate, as seen for the csrA mutant, is synonymous with a compromised ability to maintain natural plague transmission cycles. Coincidently, an hmsT mutant exhibits a similar ∼50% decrease in blockage rate ( 20 , 21 ), in agreement with the notion that csrA mutant blockage rates are due to the absence of CsrA-dependent enhancement of hmsT mRNA translation.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Thus, an ∼50% reduction in blockage rate, as seen for the csrA mutant, is synonymous with a compromised ability to maintain natural plague transmission cycles. Coincidently, an hmsT mutant exhibits a similar ∼50% decrease in blockage rate ( 20 , 21 ), in agreement with the notion that csrA mutant blockage rates are due to the absence of CsrA-dependent enhancement of hmsT mRNA translation.…”
Section: Discussionsupporting
confidence: 82%
“…Cohorts of Xenopsylla cheopis fleas were artificially infected with Y. pestis strains, and infected flea maintenance, blockage, and CFU enumeration were performed as previously described ( 21 , 78 ). To account for growth defects in the Δ csrA strain, strains were grown overnight at room temperature and then moved to 37°C at 5 h prior to infection.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The present work demonstrates that CsrA also binds to the 5′ leader region of hmsE mRNA to activate its translation, which in turn leads to greater HmsD-dependent biofilm production. Because HmsD is the predominant DGC in the flea, CsrA-dependent regulation of c-di-GMP levels through HmsD may serve as an important fine-tuning mechanism for the development of a transmissible Y. pestis infection from its flea vector and spread of plague by fleabite ( 9 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…When X . cheopis feed on highly bacteremic blood, as used for the early-phase experiments, however, several studies have shown that the blockage rate is 35 to 40% or higher [ 18 , 23 , 24 , 28 , 29 , 55 58 ].…”
Section: Discussionmentioning
confidence: 99%